Partisipasi Masyarakat Dalam Pembangunan Jalan Poros Desa di Kecamatan Panceng Kabupaten Gresik - Setiawan, Fauzi Budi (JURNAL PEMBANGUNAN WILAYAH & KOTA, 2012)
Participatory regional development strategy in Kabupaten Gresik emphasizes on infrastructure development through the Bantuan Keuangan Pembangunan Jalan Poros Desa (Village Axis Road Development Finance Aid). The study area is Kecamatan Panceng, Kabupaten Gresik. The study aims to investigate the different form and level of community participation in the project differentiated by the distance of the project from the settlements in each village. The study applied post-positivist rationalistic approach using descriptive quantitative method of research. Conclusion is drawn deductively by means of theoretical review to answer the research question:Â  how is the form and level of participation in the Village Axis Road Development project in Kecamatan Panceng Kabupaten Gresik? The study analyzes participatory form and level, and also location influence on the form and level of participation in the community, within the categories of villages.Â  Analysis confirmed a differentiation in the form and level of participation between the two categories of villages. In the first category villages, full control participation form was observed with high level of participation, meanwhile in the second category villages shared control participation form was observed, with medium level of participation.